"I Was Just Fed up of Not Being Myself": Coming out Experiences of White British Divorced and Separated Gay Fathers. Issue 3 (13th March 2021) - Clarke, Victoria; Earley, Eóin
Abstract: Before the so-called "gayby boom" in the 1990s the most common pathway to parenthood for gay men was heterosexual marriage. Since the 1990s most research on gay parenting has focused on intentional gay fathers – those parenting after coming out as gay – and the experiences of post-heterosexual divorce gay fathers (PHGF) have largely been overlooked, even though they remain the largest group of gay fathers. Furthermore, most research on this group, and on gay fathers more broadly, has been conducted in the US, with only a small handful of studies examining the experiences of gay fathers elsewhere. The current study aims to begin to address this omission by exploring the experiences of heterosexually divorced and separated UK gay fathers, focusing on their experiential journey from married, ostensibly heterosexual, men to living openly (more or less) as gay fathers. Transcripts of interviews with six white British men were analyzed using interpretative phenomenological analysis. Five themes are reported: (1) The impossibility of being openly gay; (2) "Drowning in normality"; (3) "The point of no return"; (4) The kids are alright; and (5) "It just doesn't seem to compute for people." The findings suggest that for some PHGF little has changed since the earliest research on this group of gay fathers was published in the 1970s. The men in this study had mostly experienced a tumultuous (and sometimes incomplete) journey to gay fatherhood and continued to struggle with feelings of shame and stigma.